AN OVERVIEW OF INDIAN NOVEL TRADITIONAL MEDICINAL PLANTS WITH ANTI-DIABETIC POTENTIALS - Gupta, Rahul; Bajpai, Kumar Gaurav; Johri, Samta; Saxena, A. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Diabetes mellitus is a global metabolic epidemic affecting essential biochemical activities in almost every age group. Indian literatures like Ayurveda have already mentioned herbal remediation for a number of human ailments. Among Indian traditional medicinal plants several potential anti-diabetic plants and herbs are being used as part of our diet since prehistoric time. India has a long list of native medicinal plants with confirmed blood sugar lowering property. Some of these have proved remarkable for cure of diabetes and its complications. The current paper is aimed at providing a review on clinical and experimental studies carried out on the most effective and commonly used hypoglycemic plants and herbs species from traditional Indian flora. This write–up includes hypoglycemic and anti-hyperglycemic activities of plants, active hypoglycemic compounds and constituents along with their available toxicity status.